Mathematical Concepts in Bening and Woven of Dayak Kenyah Community - Darmayasa, Jero Budi; Netiana, Irnovita; Ibut, Novina (Journal of Honai Math, 2023)
Learning mathematics requires a relevant context. Utilization of the right context can increase the connection between mathematics and other fields of science. One of the contexts that can be used is the cultural context. However, there are not many cultural contexts of the people of North Kalimantan that can be used in learning mathematics. Therefore, it is necessary to conduct qualitative research to explore mathematical concepts in Bening and Anyan of the Dayak Kenyah Community. This research is ethnographic research using the spiral model data analysis technique. Based on the results of the data analysis, it was found that there is a concept of tube volume, tube surface area, and tube nets in Bening. In addition, representations of tubes and prisms were also found in the form of Dayak Kenyah Woven. These findings can be used to enrich the process of learning mathematics at the primary or secondary education level, including at Vocational High Schools. The findings of this study can enrich the cultural context of learning mathematics and enable learning mathematics to be more meaningful.